Answering the Call to Prepare Special Education Teachers at Institutions of Catholic Higher Education - Brown, Carole W.; Celeste, Marie (Catholic Education: A Journal of Inquiry and Practice, 2006)
Concerns for social justice have called Catholics and others to be compassionate and supportive to children with disabilities by establishing schools and other learning opportunities to nurture this population. Special education as a field has developed over the past 40 years. This study examines the incidence, context, and nature of special education personnel preparation programs in institutions of Catholic higher education (ICHE). Through literature searches and web-based searches on the National Catholic College Admission Association website, a survey, and individual college websites, the study has identified 89 ICHE that offer special education degrees out of a total of 260 Catholic colleges and universities. Within the context of the demographics of ICHE, the results of this exploratory study show regional variation in special education degree programs; patterns of other education degree offerings that often occur with special education degrees and dual certification; along with information about faculty, financial aid, accreditation, practicum sites, and relationships to Catholic schools. Recommendations are offered to strengthen special education personnel preparation in areas of need, including rural areas, and special education teachers who work with culturally and linguistically diverse populations.